A new design of silybum marianum tablets by direct compression - Cianchino, Valeria Andrea (2019)
In the present paper we described a new design of herbal medicine tablets by direct compression using the ethanolic extract of Silybum marianum (L.) Gaertn. S. marianum extract is used in popular medicine as hepatoprotective herbal medicine. The alcoholic extract was obtained from seeds by soxhlet. Five pharmaceutical formulations were prepared using the extract as active principle, Aeroperl® 300 Pharma, as carrier and different diluents (CombiLac®, MicroceLac® 100, StarLac®, Cellactose® 80 and FlowLac® 90). The micromeritic properties were determined for all the physical mixtures. The results of angle of repose, compressibility and Hausner ratio indicated that the all powder mixtures had excellent flow properties and compressibility. In addition, the tablets properties and quality parameters were evaluated (weight variation, hardness, friability, disintegration test, drug content and dissolution test). One formulation (F5: herbal ethanolic extract 20 %, Aeroperl® 20 %, FlowLac® 90 57 %, Glycolate starch 2 % and magnesium stearate 1 %) showed excellent rheological properties and the best biopharmaceutical parameters in concordance with the pharmacopoeial specifications. Thus, taking into account the poor solubility of silymarin in water, this novel design could be easily applied to others poorly soluble drugs or herbal extract in order to improve its bioavailability.